LBPS 01-23 FIMASARTAN INHIBITS VSMC PROLIFERATION AND MIGRATION INDUCED BY ANGIOTENSIN II. (September 2016) - Kim, Baek-Kyung; Park, Min; Lee, Joo Young; Kim, Dal-Hyun; Myung, Jay; Choi, Jang Hyun; Jung, Hahn-Sun
Abstract : Objective: Fimasartan is a novel angiotensin II receptor blocker used for the treatment of hypertension. Angiotensin II, one of the major effectors of the rennin-angiotensin system (RAS), plays a crucial role in regulation of vascular remodeling. Inhibition of vascular smooth muscle cell (VSMC) proliferation and migration is considered a potential therapeutic mechanism to reduce the risk for atherosclerotic cardiovascular disease. In the present study, we investigated the effects of fimasartan on angiotensin II induced VSMC proliferation and migration and the molecular mechanisms involved. Design and Method: Rat VSMCs (A7r5) and Human Aortic Smooth muscle cells were obtained from ATCC. Cells were treated angiotensin II with or without fimasartan at various concentrations. Cell proliferation and migration was determined by using the BrdU incorporation assay and transwell migration assay, respectively. MAPKs (ERK1/2) activation was analysed by Western blot analysis. Results: Angiotensin II increased rat and human VSMC proliferation and treatment of fimasartan significantly inhibited cell proliferation by angiotensin II in a dose-dependent manner. Moreover, fimasartan suppressed angiotensin II induced VSMC migration to the normal level. In western blot analysis, compared with control cells, cells treated with angiotensin II showed a significant increase in ERK1/2 phosphorylation. In contrast, fimasartan significantly decreased phosphorylation of ERK1/2 induced by angiotensin II in VSMCs. Conclusions: Fimasartan inhibited the increased proliferation and migration of VSMCs by angiotensin II via the ERK1/2 pathway. Our results showed that fimasartan may be a potent inhibitor of angiotensin II induced VSMC proliferation and migration, which are important events in the progression of atherosclerosis.